(3GdJYde GdfTW hGdGHJcGQjI hbhI PcGA GdQDjI GdKGbHI (B/s - (3MSjf, eMeO YHO GdgGOjs ((3GdbGgQI (B:s (3OGQ GdYdhe ddfTQ hGdJhRjY,s, 2008)
(3jgOa gPG GdcJGH Edi JMbjb CbUi GSJaGOI ef GdNHQGJ hGdJLGQH GdYGdejI hGdOQhS GdOhdjI GdeJGMI MGdjG aj GdJYde GdfTW hPdc ef NdGd GdJQcjR Ydi Jbhje YTQGJ Hd heFGJ ef GdGSJQGJjLjGJ GdLOjOI GdNGUI HeeGQSGJ GdJYde GdfTW hGdWQb hGdCSGdjH GdLOjOI GddGReI dJMbjb GdfLGM GdCcGOjej hJcQjS GfYcGSGJ GdJYde GdfTW aj GdMjGI GdYedjI hGdGQJbGA HGdeNQLGJ GdYdejI hGdCcGOjejI(B.s
(3OcJhQ eMeO YHO GdgGOj MSjf eDSS fXQjI GdPcGAGJ GdeJYOOI aj eUQ hGdhWf GdYQHj(B.s
Keywords: (3GdJYdjes -- (3GdPcGAs -- (3GdJacjQ GdfbOjs -- (3GSJQGJjLjGJ GdJOQjSs